Reputation stretching in mutual fund starts - Chen, Hsuan-Chi; Lai, Christine W. (Journal of Banking & Finance, 2010)
This study examines the role of reputation stretching in the context of mutual funds. We show that the reputation stretching strategy increases net fund inflows to new funds run by well-performing fund managers and yields a net increase of fund inflows to fund families. Reputable fund managers exhibit one-year performance persistence for managing new funds, which can help investors assess managers when selecting funds. We also find that the decrease in information asymmetry associated with managerial reputation benefits investors by leading to an increase in new fund returns in the short run, compared to those of new funds run by managers without track records. Overall, the reputation stretching strategy benefits both investors, by reducing information asymmetry and improving investment returns, and fund families, by increasing net fund inflows to new equity funds.